Analysis of Environmental, Social and Corporate Governance Impact of Carnival Activities on Village Sustainability - Adi Maulana, Bimo; Driana Leniwati; Sri Wibawani Wahyuning Astuti (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
This research aims to find out whether the ESG concept can only be used in a company or can also be used to analyze an activity, where this activity can have an impact on society. By using an interpretive paradigm, this researcher tries to interpret the impact that occurs on carnival activities in terms of the ESG concept. Data was obtained using in-depth interviews with the organizing committee, activity participants and also local businesses involved in the activity who were key informants. The method used is a snowballing system where interview results are grouped and data reduction is carried out before being analyzed and conclusions drawn or verified. Triangulation was also carried out using different question techniques asked to ensure the validity of the data to key informants. By using triangulation techniques, researchers ensure that the data obtained is valid. The results of this research found that there are many impacts that occur in carnival activities which are reviewed with the ESG concept which can later be used as something for the sustainability of the village and can also be a reason in making decisions for the sustainability of the village and also for the sustainability of this activity. In other cases The impact resulting from the concept that has been applied to this activity can be seen from the environmental, social and environmental impacts of this activity also governance.